Small Bodies Near and Far (SBNAF): A benchmark study on physical and thermal properties of small bodies in the Solar System. Issue 8 (15th October 2018) - Müller, T.G.; Marciniak, A.; Kiss, Cs.; Duffard, R.; Alí-Lagoa, V.; Bartczak, P.; Butkiewicz-Bąk, M.; Dudziński, G.; Fernández-Valenzuela, E.; Marton, G.; Morales, N.; Ortiz, J.-L.; et al.
Abstract: The combination of visible and thermal data from the ground and astrophysics space missions is key to improving the scientific understanding of near-Earth, main-belt, trojans, centaurs, and trans-Neptunian objects. To get full information on a small sample of selected bodies we combine different methods and techniques: lightcurve inversion, stellar occultations, thermophysical modelling, radiometric methods, radar ranging and adaptive optics imaging. The SBNAF project will derive size, spin and shape, thermal inertia, surface roughness, and in some cases bulk densities and even internal structure and composition, for objects out to the most distant regions in the Solar System. The applications to objects with ground-truth information allows us to advance the techniques beyond the current state-of-the-art and to assess the limitations of each method. We present results from our project's first phase: the analysis of combined Herschel-KeplerK2 data and Herschel-occultation data for TNOs; synergy studies on large MBAs from combined high-quality visual and thermal data; establishment of well-known asteroids as celestial calibrators for far-infrared, sub-millimetre, and millimetre projects; first results on near-Earth asteroids properties from combined lightcurve, radar and thermal measurements, as well as the Hayabusa-2 mission target characterisation. We also introduce public web-services and tools for studies of small bodies in general.